MAQOMAT DAN AKHWAL SERTA RELEVANSINYA DALAM KEHIDUPAN - Daman (STAI Darussalam Lampung, 2023)
Abstrak The rapid development of science and technology has both positive and negative effects on life. Mental and moral damage is one of the negative impacts that occur when humans live without a purpose. Bringing up the noble crimes of drug abuse, juvenile delinquency, etc. These problems make people both the cause and the people responsible for solving them. Whereas conceptually, the issue is closely related to personality issues or in Islam it is called morals. The purpose of this study is to describe and examine Maqomat and Akhwal their relevance in everyday life. This search is a literature search, so that the data source is in the form of library materials such as books, journals, and scientific articles. Usually data collection in this study uses library research methods which are analyzed using data analysis and description methods. The results of this study are maqamat and ahwal in Sufism, of which there are seven maqamat, namely: repentance, wara, zuhud, poverty. , patient , confident and fun. Ahwal is muraqabah, mahabbah, khauf, raja', syauq, tuma'ninah, musyahadah, and of course. The relevance of the concept of Sufism in today's life is that maqomat and ahwal will be guidelines for achieving the right approach to God.